Mouse mission - Breitrose, Prudence E. (Disney-Hyperion, 2015)
"When a timber company threatens to cut down the rainforest on the island of Marisco, Megan's mom leads the effort to save it, with the help of the Mouse Nation. The mission takes the family (and mice) to England, where the trail leads to a duke's palace full of dangerous humans--and helpful British mice"--